Beginning Java Web development : an introduction to lightweight development, deployment, and security - Kalin, Martin (O'Reilly, 2016)
"In this Beginning Java Web Development training course, expert author Martin Kalin will teach you everything you need to know about Java web development. This course is designed for users that are familiar with writing, compiling, and executing Java applications. You will start by learning about web apps and databases using JSP and POJOs. From there, Martin will teach you about servlets, including the flow of control in servlets, code analysis, and concurrency issues in Java web apps. This video tutorial also features an example of a shopping cart as a web app, where you will learn how to extend and improve the shopping cart web app. Finally, you will learn about web app security, including wire-level security and user authentication and role authorization. Once you have completed this computer based training course, you will have learned everything you need to know about Java web development. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.